Scientific Cooperation Between Polish People’s Republic and the Second Yugoslavia - Małczak , Leszek (Poznańskie Studia Slawistyczne, 2020)
Scientific connections between Polish People’s Republic and The Second Yugoslavia were a very important element of the bilateral relations between both countries. The mechanisms and rules of the scientific cooperation were similar to the rules and mechanisms of the cultural cooperation and faced the same constraints and possibilities. Types of institutions existing in the field of culture had their correspondences in the field of science and education. Developing of the scientific cooperation was not a strategic aim for both countries in the interwar period as well as during the Communism due to the situation on the international political scene. In the era of globalization, in the context of international scientific cooperation, interslavic relations has become the weakest in the last two centuries. Nowadays, even more than before, the scientific cooperation between all Slavic countries depends on individuals and their involvement.